Diferencia en el perfil clínico y resultados terapéuticos en niños y adolescentes diagnosticados con VIH que reciben diferentes regímenes de tratamiento antirretroviral y cómo influye esto en su pronóstico a largo plazo, en Loreto: un análisis retrospectivo de 10 años (2014-2024), año 2024 - Ynga Hidalgo, Genoveva Alejandra (2025)
Over the past ten years, the AIDS epidemic has increased among women of reproductive age worldwide, increasing the number of children at risk of mother-to-child transmission (MTCT) of HIV-1. In Eastern and Southern Africa, of the 1.4 million HIV-positive children, only 51% are receiving antiretroviral therapy (ART), the overall suppression rate is estimated to be 47% although the suppression rate among children is not documented. In Uganda, approximately 95,000 children are living with HIV, 47% of them are receiving ART, with a non-suppression rate of 60.1%, which is higher than that observed among adults (40.4%) and also well above the national target of 10%. The HIV epidemic in Peru is concentrated, as it presents higher transmission and prevalence in key populations.; According to the National Center for Epidemiology, Prevention and Disease Control, it was estimated that by 2023, around 110,058 people would be living with HIV infection, with a prevalence of 0.39% in adults aged 15 to 49 years, and a higher prevalence in the population of men who have sex with men by 10.7% and in transgender women by up to 33.4%. The departments that show the highest incidence rates for HIV are those in the eastern, coastal (mainly Lima as the capital and borders) and central parts of the country, while AIDS cases are in the eastern and northern coast of the country. In 2023, the male/female ratio was 3.7, lower than that obtained in 2022, which was 4.0. Although the proportion of HIV-positive children (under 15 years of age) receiving antiretroviral therapy (ART) has increased in recent years, up to 60% of children who start ART do not achieve virological suppression.